2007
DOI: 10.1074/jbc.m703616200
|View full text |Cite
|
Sign up to set email alerts
|

Highly Conserved Sequences Mediate the Dynamic Interplay of Basic Helix-Loop-Helix Proteins Regulating Retinogenesis

Abstract: The atonal homolog 5 (ATH5) protein is central to the transcriptional network regulating the specification of retinal ganglion cells, and its expression comes under the spatiotemporal control of several basic helix-loop-helix (bHLH) proteins in the course of retina development. Monitoring the in vivo occupancy of the ATH5 promoter by the ATH5, Ngn2, and NeuroM proteins and analyzing the DNA motifs they bind, we show that three evolutionarily conserved E-boxes are required for the bHLH proteins to control the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 31 publications
1
24
1
Order By: Relevance
“…We cannot exclude that a number of bHLH might compete to occupy the conserved Six6 E-box and control different phases of Six6 expression, as reported for Ath5 regulation in RGCs (Hernandez et al, 2007). Nevertheless, our results support a highly specific role of the NeuroD-E47 heterodimer in the binding and transactivation of the E-box in the Six6 enhancer.…”
Section: Research Articlecontrasting
confidence: 34%
See 1 more Smart Citation
“…We cannot exclude that a number of bHLH might compete to occupy the conserved Six6 E-box and control different phases of Six6 expression, as reported for Ath5 regulation in RGCs (Hernandez et al, 2007). Nevertheless, our results support a highly specific role of the NeuroD-E47 heterodimer in the binding and transactivation of the E-box in the Six6 enhancer.…”
Section: Research Articlecontrasting
confidence: 34%
“…Development 137 (14) Different subfamilies of bHLH proteins can form heterodimers and recognize the same canonical E-box sequence (Hernandez et al, 2007;Powell and Jarman, 2008). We cannot exclude that a number of bHLH might compete to occupy the conserved Six6 E-box and control different phases of Six6 expression, as reported for Ath5 regulation in RGCs (Hernandez et al, 2007).…”
Section: Research Articlementioning
confidence: 99%
“…Despite the fact that Hes5.3 expression is detected in the whole subset of Atoh7-expressing progenitor cells, only 25-30% of them upregulate Atoh7 and enter this lineage in chick between E3 and E5 (Chiodini et al, 2013;Matter-Sadzinski et al, 2005). This low efficiency of RGC production at early stages is attributed to the negative effect of HES1 on Atoh7 cis-acting regulatory elements (Hernandez et al, 2007), hence keeping transcription of the Atoh7 gene at a low level in progenitor cells. Thus, we could expect that, at the onset of Atoh7 expression in pigeon, a larger subset of cells express Atoh7 at high levels.…”
Section: Notch Signalling and Patterning Of The Retinamentioning
confidence: 92%
“…HES1 is expressed in the developing retina and it represses Atoh7 and Ngn2 expression (Hernandez et al, 2007;Lee et al, 2005;Matter-Sadzinski et al, 2005). We examined whether prolonged expression of HES1 could account for delaying neuronal differentiation in pigeon.…”
Section: Notch Signalling and Patterning Of The Retinamentioning
confidence: 99%
“…Whereas site occupancy and functional analyses have shown that the Ngn2 (Neurog2) and Atoh7 basic helix-loop-helix (bHLH) proteins are required for transcription of the chicken Atoh7 gene (Hernandez et al, 2007;Matter-Sadzinski et al, 2001;Matter-Sadzinski et al, 2005;Skowronska-Krawczyk et al, 2004), the late onset of Ngn2 expression and the continued expression of the mutated Atoh7 gene in suggested that these factors are not involved in the regulation of Atoh7 in mouse (Brown et al, 1998;Brown et al, 2001;Hutcheson et al, 2005;Wang et al, 2001). The differences between mouse and chicken in the regulation of Atoh7 are used in the present study to compare the function of evolutionarily conserved regulatory sequences that include several bHLH binding sites.…”
Section: Introductionmentioning
confidence: 99%